Monitoring biomass burning emissions using satellite imagery for southern Africa - McKechnie, Candice-Joy (My University, 2011)
Biomass burning contributes significantly to the global concentrations of greenhouse gases and aerosols in the atmosphere (Fishman et al., 2003, Kaufman et al., 1998). The African continent is responsible for a large proportion of these emissions, especially due to savanna burning (Scholes et al., 1996a). Due to extensive burning on the African continent, monitoring fires and quantifying their emissions has become important and relevant especially in southern Africa. Moderate Resolution Imaging Spectrometer (MODIS) daily active fire counts are used as a proxy for burning to provide insight into spatial and temporal distribution of fires and estimate biomass burning emissions over southern Africa. The burning season in southern Africa occurs during winter and spring and coincides with the dry season (May to October). Fires start in the western part of the sub-continent in March and spreads south and east throughout the burning season. Conditions are most conducive to fire occurrence when a particularly wet season follows an extended or particularly dry season. Anthropogenic burning is emphasised by the inconsistent correlation between rainfall and burning. The pattern for interannual and seasonal burning emissions is similar for carbon dioxide (CO2), carbon monoxide (CO), methane (CH4), ammonia (NH3), total particulate carbon (TPC) and organic particulate carbon (OPC), with greatest quantities emitted from woodland fires, followed by forest and savanna, and lastly agriculture. Biomass burning emissions (189 TgCO2.yr-1) constitute approximately one quarter of the CO2 emissions released by the industrial and the energy sector combined (843 TgCO2.yr-1) in South Africa. This study estimates twice the amount of particulates (610.yr-1) released by biomass burning in South Africa as the industrial and energy sector combined (331. yr-1). CH4 emissions from biomass burning (approximately 463 GgCH4.yr-1) makes a considerable contribution to total CH4 emissions (approximately 844 GgCH4.yr-1) for South Africa. The accuracy of greenhouse gas and aerosol estimates can be refined by using improved burned area estimates, consistent vegetation maps and standardised emission factors.